Legal Sanctions Against Members Of The District Election Committee (PPK) Who Commit Election Crimes - Mariana Harahap; Marjan Miharja (SEAN Institute, 2024)
In the context of elections as an implementation of people's sovereignty, election law enforcement is interpreted as a situation where mechanisms are available to safeguard the people's right to vote. So that the electoral justice system is expected to be able to guarantee everyone's right to file a complaint if the party concerned feels disadvantaged as a result of certain actions being taken or not taken by the organizers or parties involved in the election. There were violations committed by members of the District Election Committee (PPK) whose case was decided by the Makassar High Court Number 492/PID.S.PEMILU/2024/PT MKS. The formulation of the problem discussed is: 1) What are the legal sanctions against PPK members who are proven to have changed the recapitulation of vote results from the election? and 2) What is the analysis of the Decision of the Makassar High Court Number 492/PID.S/PEMILU/2024/PT MKS regarding members of the District Election Committee which changed the recapitulation of the results of the calculation of votes in the election? The research method used is a normative juridical method, namely research that prioritizes library data, namely research on secondary data. Secondary data can be in the form of primary, secondary or tertiary legal materials. Based on the results of the research, the author concludes that legal sanctions against PPK members who are proven to have changed the recapitulation of vote results from the election, can be sentenced to prison as proven in the decision of the Makassar High Court Number 492/PID.S/PEMILU/2024/PT MKS which gave the verdict to the defendant DZUL FIQRI Alis ZUL Bin SABER TUPPU mentioned above, was legally and convincingly proven guilty of committing the crime of